10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
OBJECTIVES: To evaluate the agreement of a commercially available point-of-care FCoV RT-qPCR assay and external laboratories RT-qPCR testing in cats with effusive and non-effusive FIP, and in cats with other diseases presenting with similar clinical signs. METHODS: Client-owned cats suspected of FIP were enrolled with owner consent. Effusions and ultrasound-guided fine-needle aspirates (FNAs) from liver, spleen, or mesenteric lymph nodes were collected, split, and analysed using both a point-of-care RT-qPCR and an external laboratory RT-qPCR. FIP was diagnosed based on AAFP/EveryCat guidelines. Sensitivity and negative predictive values were calculated, agreement assessed with Cohen's kappa, paired differences tested with McNemar's test, and correlation of crossing point (Cp) values analysed using Pearson's coefficient and paired t-tests. RESULTS: One hundred cats were included (effusions n = 62, FNAs n = 38). Overall agreement between assays was substantial (κ = 0.73), with near-perfect concordance for effusions (κ = 0.81) and lower agreement for FNAs (κ = 0.61). Relative sensitivity was highest in effusions (98.1% point-of-care, 92.3% external) and lower in FNAs (63.3-64.5%), with negative predictive values showing similar trends. Cp values were moderately correlated between assays, with minor mean differences (~1 cycle). CONCLUSION AND RELEVANCE: The point-of-care FCoV RT-qPCR assay is a practical and reliable tool and shows very good agreement with external reference laboratory RT-qPCR testing. FNAs remain useful when effusions are unavailable but carry higher risk of false negatives likely due to low viral loads and heterogeneous distribution. Point-of-care testing offers rapid turnaround, supporting timely clinical decision-making, but results must be interpreted alongside clinical presentation and other diagnostics.